ANÁLISE ESTATÍSTICA DO RISCO DE MORTE POR INFECÇÃO HOSPITALAR EM GOIÂNIA - Barros, Victor Freitas de Azeredo; Menezes, José Elmo de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611706840 The Hospital Infection is considered a serious problem, growing both in incidence as incomplexity, generating many kinds of social and economic implications. The control of this mustbe based the all health professionals. The solution is strengthening the Commission for HospitalInfection Control (CHIC). Based on this problem is proposed mathematical modeling of the risk of aperson collapse a Hospital Infection and the risk of death of a person with Hospital Infection. Forthis, we will do a data survey in IBGE, ANVISA, and others, and we will do with this data a statistictreatment. As theoretical tool, we will use the Theory of Survival Analysis, and too the statisticalmodels discussed in this theory. As a computational tool, we will use the R program, free softwarethat provides excellent means for statistics analysis and with high quality of graphical features.